Rasio Likuiditas dalam Mengukur Penyaluran Kredit di PT Bank BRI Tbk Unit Cihaurbeuti periode 2015-2018 - Santi Widiawati; Dimas Jatnika (LPPM POLITEKNIK LP3I BANDUNG, 2019)
This paper discusses of bank liquidity ratio on the development of commercial credit at PT Bank BRI Unit Cihaurbeuti. The issue of this research problem is: how big is the effect of liquidity on credit ratio at PT Bank BRI Unit Cihaubeuti period 2015-2018. The type of research used is descriptive research, this analysis gives an overview of the specific characteristics of the data that has been collected. The Data will be analyzed, resulting in an overview of what is the most dominant factor in encouraging bank customers to take commercial credit in BRI bank. This research is relatively quantitative with an associative approach. The research is a technique of data collection conducted is a technical documentation based on the financial statements that are given directly by the BRI Bank through direct visits to the Bank. Furthermore, processing techniques and data analysis were conducted through classical assumption tests, simple linear regression analyses, and hypothesis testing (Test T). The results showed that the influence of bank liquidity on the development of commercial credit is seen from the increase in the four years backwards, which is in tandem with the increase in liquidity of banks that demonstrates the relationship or influence . The test results of the classical assumption of the study showed the results of normal distributed data and free of correlation and coefficient of determination. Furthermore, the result of the hypothesis test results in the test that the bank's liquidity ratio has a partial effect on commercial credit